Sustentabilidade fiscal do investimento público para os estados brasileiros - Carvalho, Jessé Melo de (2017)
This study analyzes the sustainability of the Brazilian State Investment Policy in the period 2008-2016 from the point of view of their impact on the public sector expenditures. The hypothesis underlying the study establishes that an investment policy that raises the Cost/Net Revenue relation will be unsustainable. Otherwise, is considered sustainable the investment policy which encourages a growth in revenues that exceeds the corresponding cost increase. In order to investigate this hypothesis, fiscal reaction functions of costs for lagged investments are estimated as a proportion of the state Net Revenue, in a panel with data between 2008 and 2016, for the 27 units of the federation, extracted from publications of the National Treasury Office. Estimates obtained by Two-Stage Least Squares (2SLS) Regression Analysis for the settled public expenses classify the investment policy as innocuous, although this strategy is effective when using the scheduled public expenses. As conclusion, the results explain that the effectiveness of the investment policy increases according as the allocation of resources gets close to planning and, therefore, reinforces the importance of an efficient management of the public machine, especially for the recovery of the investments that were deteriorated with the recent fiscal crisis.